K [star] (892)0 and ϕ(1020) production at midrapidity in pp collisions at √s=8 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Klewin, Sebastian; Köhler, Markus Konrad; Leardini, Lucia; Martin, Nicole Alice; et al. (Physical review, 2020)
The production of K∗(892)0 and ϕ(1020) in pp collisions at √s=8 TeV was measured by using Run 1 data collected by the ALICE collaboration at the CERN Large Hadron Collider (LHC). The pT-differential yields d2N/dydpT in the range 0<pT<20 GeV/c for K*0 and 0.4<pT<16 GeV/c for ϕ have been measured at midrapidity, |y|<0.5. Moreover, improved measurements of the K*0(892) and ϕ(1020) at √s=7 TeV are presented. The collision energy dependence of pT distributions, pT-integrated yields, and particle ratios in inelastic pp collisions are examined. The results are also compared with different collision systems. The values of the particle ratios are found to be similar to those measured at other LHC energies. In pp collisions a hardening of the particle spectra is observed with increasing energy, but at the same time it is also observed that the relative particle abundances are independent of the collision energy. The pT-differential yields of K*0 and ϕ in pp collisions at √s=8 TeV are compared with the expectations of different Monte Carlo event generators.